Analisis Pengaruh Harga Batu Bara Acuan, Suku Bunga BI 7-Day Repo Rate & Nilai Tukar Terhadap Indeks Harga Saham Sektor Energi Pada Bursa Efek Indonesia (BEI) - Alfin Fitra Perdana; Niniek Imaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The Indonesian capital market in recent years has become a hot topic of discussion among the public, especially the stock market. The energy sector stock price index is an index that has a significant increase in 2021-2022. This index has tripled from the price first released by the IDX. This is a rare phenomenon, so research is needed to find out what factors influence the movement of the energy sector stock price index. The purpose of this study was to see the effect of the reference coal price, the BI 7-day repo rate, the exchange rate on the energy sector stock price index. In this study the analysis technique used is multiple linear regression analysis technique. The data taken for the study is monthly data over a period of 24 months. Starting from January 2021 to December 2022. The results show that partially the reference coal price variable has a significant effect on the Energy Sector stock price index. Partially, the BI 7-day repo rate variable has a significant effect on the Energy Sector stock price index. Partially the exchange rate variable has no significant effect on the Energy Sector stock price index. Keywords : Reference Coal Price; Reference Interest Rate; Exchange rate; Energy Sector Stocks